Plasma trimethylamine-N-oxide, its precursors and risk of cardiovascular events in patients with acute coronary syndrome: Mediating effects of renal function - Raul Sanchez-Gimenez; Raul Sanchez-Gimenez; Raul Sanchez-Gimenez; Óscar M. Peiró; Óscar M. Peiró; Óscar M. Peiró; Gil Bonet; Gil Bonet; Gil Bonet; Anna Carrasquer; Anna Carrasquer; Anna Carrasquer; et al. (Frontiers in Cardiovascular Medicine, 2022)
AimsTo examine associations of the gut microbial metabolite trimethylamine-N-oxide (TMAO) and its precursors with risk of cardiovascular events in acute coronary syndrome (ACS), and determine whether these associations were mediated by renal function.MethodsIn this prospective cohort study, we included 309 patients with ACS. During a mean follow-up of 6.7 years, 131 patients developed major adverse cardiovascular events (MACE) (myocardial infarction, hospitalization for heart failure, and all-cause mortality). Plasma concentrations of TMAO, trimethylamine (TMA), choline, betaine, dimethylglycine and L-carnitine were profiled by liquid chromatography tandem mass spectrometry. Hazard ratios were estimated with multivariable Cox regression models. The mediating role of estimated glomerular filtration rate (eGFR) was tested under a counterfactual framework.ResultsAfter adjustment for traditional cardiovascular risk factors and medications, participants in the highest tertile vs. the lowest tertile of baseline TMAO and dimethylglycine concentrations had a higher risk of MACE [(HR: 1.83; 95% CI: 1.08, 3.09) and (HR: 2.26; 95% CI: 1.17, 3.99), respectively]. However, with regards to TMAO these associations were no longer significant, whereas for dimethylglycine, the associations were attenuated after additional adjustment for eGFR. eGFR mediated the associations of TMAO (58%) and dimethylglycine (32%) with MACE incidence. The associations between dimethylglycine and incident MACE were confirmed in an internal validation. No significant associations were found for TMA, choline, betaine and L-carnitine.ConclusionThese findings suggest that renal function may be a key mediator in the association of plasma TMAO with the development of cardiovascular events after ACS. The present findings also support a role of dimethylglycine in the pathogenesis of MACE, which may be mediated, at least partially, by renal function.